A review of the family Sphaeronectidae (Class Hydrozoa, Order Siphonophora), with the description of three new species - Pugh, P. R. (Zootaxa, 2009)
The last reviewer of the family Sphaeronectidae (Siphonophora, Calycophorae) (Carré, 1968c) considered that it consisted of a single genus, Sphaeronectes, containing five species; three of which had been recently described by himself. For the other two species there had been much nomenclatural confusion in the past, as is herein reviewed. It is considered that for one of these species the name Sphaeronectes koellikeri Huxley (1859) has priority over the name currently in usage, that is S. gracilis (Claus, 1873; 1874). In addition the status of S. brevitruncata (Chun, 1888) is reconsidered and the species considered valid, with S. japonica (Stepanjants, 1967) being considered as a likely junior synonym of it. Three new Sphaeronectes species, S. christiansonae sp. nov., S. haddocki sp. nov. and S. tiburonae sp. nov., are described, and the systematic position of the genus reconsidered in the light of preliminary molecular phylogenetic data.